Assessment of present-day heavy metals pollution and factors controlling surface water chemistry of three Western Siberian sphagnum-dominated raised bogs - Kharanzhevskaya, Yulia A.; Gashkova, Lyudmila P.; Sinyutkina, Anna A.; Kvasnikova, Zoya N. (Water)
This study investigated the heavy metal concentrations in bog and stream water compared to present-day atmospheric deposition, and concentrations in peat and vegetation within three typical raised bogs in Western Siberia located in urban area, close to oil and gas facilities and in the natural background area. Our data showed that elevated heavy metals deposition occurs not only near industrial centres but also in remote areas, which is a sign of regional atmospheric deposition of heavy metals associated with long-range transport and wildfires. Present-day atmospheric depositions of heavy metals are not always consistent with their contents in waters, and the content of Zn, Pb, Cu and Cd in waters is more correlated with their concentrations in vegetation and in the upper peat layer; this indicates a significant role of biological processes in heavy metal cycling. Temperature plays an important role in increasing the mobility and vegetation uptake of heavy metals. Heavy metals removal is largely determined by the size of the bog and its stage of development, which determines bog–river interaction. The seasonal catchment-scale budget indicated that 80–97% of Zn and Pb and 47–74% of Cu and Cd from atmospheric inputs remained within the catchments.